Multiscale analysis of thermomechanical stresses in double wall transpiration cooling systems for gas turbine blades. (1st October 2021) - Skamniotis, Christos; Courtis, Matthew; Cocks, Alan C.F.
Highlights: The new double wall transpiration cooling systems experience high stresses. Thermal stresses are weakly sensitive to 2 nd order wall temperature variations. They mainly depend on the wall thickness ratio and wall temperature mismatch. Centrifugal (CF) loading causes higher stress concentrations than thermal loading. Critical stresses at film holes reduce when CF and thermal loading are combined. Abstract: Double wall transpiration cooling (DWTC) is a new technology that allows the gas turbine inlet temperatures to be increased beyond current levels to promote higher engine efficiency. DWTC systems consist of outer hot and inner cooler walls, connected by pedestals, which contain film cooling and impingement holes, respectively. In order to employ these new systems, an evaluation of the stresses that drive fatigue and ratchetting at critical stress raisers is essential. We present a modelling framework which combines Computational Fluid Dynamics (CFD)-heat transfer solutions for the temperature field in DWTC systems, with theoretical and Finite Element (FE) elastic solutions for the thermal (T) stress and centrifugal (CF) stress fields. We demonstrate that uniaxial tensile CF loading causes much higher stress concentration factors (SCF) at cooling holes and wall-connecting pedestals than the thermally induced biaxial stresses. A theoretical framework is developed, supported by FE studies, that captures the dependence of the SCF on important geometric parameters, such as wall thicknesses, pedestal height and hole size, spacing and inclination angle, which provides important information for the optimisation of these systems. A key observation of relevance to both conventional and non-conventional turbine blade designs, is that the superposition of tensile CF stresses to compressive T stresses is beneficial for the performance at the critical film hole features; for double wall blades, however, the superposition degrades the performance at impingement holes and pedestals, as in these locations the T stresses are also tensile. These stresses can be balanced by using an optimal wall thickness ratio. Our elastic solutions can be readily used in analyses for predicting structural ratchet boundaries based on shakedown theory and the local cyclic strain range that drives thermomechanical fatigue in DWTC systems. Graphical abstract: Image, graphical abstract